Broader Impacts of the Metasomatic Underplating Hypothesis. (7th November 2019) - Park, Jeffrey; Rye, Danny M.
Abstract: The "metasomatic underplating" hypothesis argues that crustal fractures develop during hot spot magma ascent to allow seawater to infiltrate and to serpentinize the sub‐Moho mantle. Published seismic velocities and layer thicknesses support estimates that 1 km of seawater could be chemically bound within an underplated layer, which may require 2–4 Myr to mature. If a serpentinized mantle layer underlies hot spot tracks and/or aseismic ridges, their buoyancy can induce flat‐slab behavior within subduction zones (e.g., beneath central Chile and Peru), weaken slab rheology, and foster slab tears. During serpentinization, metasomatic underplating would produce more serpentine and talc and less brucite and magnetite, if seawater equilibrates with silica in the gabbroic oceanic crust as it descends to the Moho. The restricted solubility of carbonate with temperature may induce seawater CO2 to sequester in the crust as carbonate concretions or intergrowths. Consumption of seawater H2 O by serpentinization raises its salinity so that Fe cations stabilize in chloride complexes and depart the open system. Alkali cations in seawater contribute to the sodic metasomatism of pyroxenes, analogous to alterations observed in abyssal peridotites. Plain Language Summary: A 7‐ to 10‐km layer of rock of intermediate seismic velocities and strong anisotropy beneath volcanic hot spot islands has typically been attributed to magmatic and diapiric models that make physical predictions that are not observed. The metasomatic‐underplating hypothesis posits that seawater descends cracks to serpentinize the sub‐Moho mantle. The hypothesis is yet to be properly confirmed, but one can assess its broader impacts and form testable predictions. If seawater penetrates the oceanic crust as a byproduct of hot spot volcanism, exchanging seawater carbonate for silica, and carries this silica deeper to serpentinize the uppermost mantle, a surprising collection of geophysical and geochemical observations can be explained. Metasomatized crust and mantle beneath hot spot tracks become buoyant ribbons trapped within cool dense slabs, and are likely avenues for water and CO2 to reach the mantle transition zone. Key Points: Metasomatic underplating posits that seawater serpentinizes the sub‐Moho mantle at many hot spots to thicknesses of 5–10 km Seawater should exchange carbonate for silica while descending to the Moho, consistent with carbonate veins in drill cores of the aseismic Cocos Ridge Subduction of hot spot tracks correlates with flat‐slab subduction; the buoyancy of the serpentinized underplated layer should encourage it